An Enhanced Electroporator Design for Pulse Generation - Pachamuthu, S.; Najumnissa, D.; Sankaranarayanan, K.; Ramachandran, R. P. (Engineering, Technology & Applied Science Research, 2021)
An electroporator is an instrument used for delivering electrical pulses to a tumor. In this work, an electroporator consisting of three main system blocks, namely High Voltage (HV) source, nanosecond (ns) switching, and pulse generation, was designed, developed, and evaluated to generate high voltage ns pulses to treat tumors. The high-voltage source block was used to convert the 9.6V DC from the battery to a variable HV output and store this charge for later use. The ns switching block contained a MOSFET-based low-side switch which applies short ns pulses to the load. The pulse generation block generates short ns pulses and supplies the adequate current to turn on the MOSFET at a quicker rate aiding the application of these pulses to the load. This process was simulated using PSpice software and the results are presented.